The methyl jasmonate-responsive transcription factor SmMYB1 promotes phenolic acid biosynthesis in Salvia miltiorrhiza. (1st January 2021) - Zhou, Wei; Shi, Min; Deng, Changping; Lu, Sunjie; Huang, Fenfen; Wang, Yao; Kai, Guoyin
Abstract: Water-soluble phenolic acids are major bioactive compounds in the medicinal plant species Salvia miltiorrhiza . Phenolic acid biosynthesis is induced by methyl jasmonate (MeJA) in this important Chinese herb. Here, we investigated the mechanism underlying this induction by analyzing a transcriptome library of S. miltiorrhiza in response to MeJA. Global transcriptome analysis identified the MeJA-responsive R2R3-MYB transcription factor-encoding gene SmMYB1 . Overexpressing SmMYB1 significantly promoted phenolic acid accumulation and upregulated the expression of genes encoding key enzymes in the phenolic acid biosynthesis pathway, including cytochrome P450-dependent monooxygenase (CYP98A14). Dual-luciferase (dual-LUC) assays and/or an electrophoretic mobility shift assays (EMSAs) indicated that SmMYB1 activated the expression of CYP98A14, as well as the expression of genes encoding anthocyanin biosynthesis pathway enzymes, including chalcone isomerase (CHI) and anthocyanidin synthase (ANS). In addition, SmMYB1 was shown to interact with SmMYC2 to additively promote CYP98A14 expression compared to the action of SmMYB1 alone. Taken together, these results demonstrate that SmMYB1 is an activator that improves the accumulation of phenolic acids and anthocyanins in S. miltiorrhiza . These findings lay the foundation for in-depth studies of the molecular mechanism underlying MeJA-mediated phenolic acid biosynthesis and for the metabolic engineering of bioactive ingredients in S. miltiorrhiza .